Occurrence of the Enigmatic Bivalved Fossil Apistoconcha in the Lower Cambrian of Southeast Shaanxi, North China Platform. (March 2014) - Li, Guoxiang; Zhang, Zhifei; Hua, Hong; Yang, Huining
Abstract : The early Cambrian calcareous skeletal fossil Apistoconcha Conway Morris is characterized by its two valves having posterior teeth and internal umbonal cavities. It has been reported from lower Cambrian Botomian-equivalent carbonate rocks in Australia, Mongolia, and Greenland. Here we report a new occurrence of Apistoconcha in the lower Cambrian Xinji Formation of Luonan, southeast Shaanxi Province, North China Platform. Based on material (five ventral and four dorsal valves) from the Xinji Formation, Apistoconcha cf. apheles is systematically described and the taxonomic affinity of Apistoconcha is discussed. The shell of Apistoconcha possesses an 'antero-posterior' plane of bilateral symmetry, and its two valves apparently articulated in life, although the tooth-like structures and pits show little resemblance to the teeth and sockets, respectively, of bivalved shells of rhynchonelliform brachiopods or pelecypods. Apistoconcha cannot be assigned to the crown groups of either brachiopods or mollusks, even though functional morphological analysis indicates that Apistoconcha may be a 'stem-group brachiopod'. Unlike Apistoconcha, the morphologically similar Tianzhushanella Liu is known only from a single type of valve lacking posterior teeth and pits. Tianzhushanella may represent either a univalved animal or a bivalved animal, the other valve of which has not yet been identified. Even though both Apistoconcha and Tianzhushanella may represent stem-group brachiopods, they probably correspond to different stages of brachiopod evolution. Thus assignment of Apistoconcha and Tianzhushanella to the same family (Tianzhushanellidae) may obscure their phylogenic implications.